Pattern of Antibiotics Use at the Primary Health Care Level of Bangladesh: Survey Report-1 - Hasan, SM Raquibul; Hossain, Md Mokarram; Akter, Raushanara; Karim, SM Hasibul; Haque, Shamsul; Kamaluddin, Md; Ghani, Abdul (Stamford Journal of Pharmaceutical Sciences, 2010)
Although Bangladesh has made substantial progress in drug manufacturing since the introduction of its National Drug Policy (NDP) in 1982, irrational use of drugs, inappropriate prescribing, inadequate access to essential drugs and unjustified self medication are a few of a range of problems that are affecting the total health care system seriously. Taking this in view, a survey project has been designed to conduct nationwide to explore the pattern of antibiotics use at the primary health care level in Bangladesh using carefully constructed questionnaires containing questions covering both antibiotic prescription habit of the physicians and patients’ response to antibiotic use. In the first phase of this effort, 20 Upazila Health Complexes and the Union Health Centres thereunder each of Dhaka and Chittagong division were randomly surveyed. From physician survey it was evident that 55.57% of the doctors prescribe antibiotics in suspected infection while only 33.46% of them prescribe antibiotics in confirmed cases. 40.22% of doctors prescribe antibiotics in cold and fever before any diagnostic test. Moreover, 37.31% of doctors prescribe antibiotics for pleasing the patients whereas 62.44% denied such undue influence. Doctors seldom receive feedback of completion of course of antibiotic therapy by patients. Cephalosporin was found to be the most (26.9%) preferred antibiotic in case of empirical therapy. On the other hand, it was evident from patient survey that cold, fever and acute respiratory infection (ARI) were prevalent (39.78%) causes that brought the patients to physician. 60.1 % of the patients reported that they get essential antibiotics from hospital free of cost while 24.5% of them complained that they do not get antibiotics from hospital. 34.76% of the patients reported that they complete the course of antibiotic therapy by buying antibiotics from the market whereas 56.14% of them do not buy the full course and stop taking medicine (53.46%) as soon as symptoms subside. The results of the present survey indicate that antibiotics are widely and inappropriately used without following standard guidelines or based on any rationality. This is an alarming situation, which should be properly taken care of by the relevant authority to save the people from growing antibiotic resistance. Key words: Bangladesh; Rational use; Antibiotics; Primary health care. DOI: 10.3329/sjps.v2i1.5809 Stamford Journal of Pharmaceutical Sciences Vol.2(1) 2009: 1-7